Komunikasi Interpersonal Komunitas Pelita dalam Membangun Toleransi Beragama - Riyadi, Agus; Wigati, Yunika Indah (Jurnal Komunikasi Islam, 2020)
This article discusses religious tolerance in the perspective of interpersonal communication. This research was conducted using descriptive qualitative methods through a phenomenological approach. The results showed that inter-personal communication patterns that occurred between members of the Pelita community in building religious tole-rance based on interpersonal competence, friendship asso-ciations, professional relationships, and websites for inter-personal relationships. While romantic communication pat-terns and family relationships did not appear. This is because Pelita was medium for people meeting from various religious backgrounds who were not tied based on genetic, but com-munication amongst members relying on the social and national based relationship.